The Information Society and Action Multiculturalism - Morales Campos, Estela (2004)
No one can speak of the XXI century society without relating to the use of information and social access to telecommunications and computing to meet the demands of new citizens. In the countries of Latin America, where access to information and technology is not easy, it requires that these elements are part of the responsibilities of individuals and governments to conform policies and public programs and private education, culture and science.